MEASUREMENT OF THE AVERAGE LIFETIME OF B-HADRONS - Adriani, O; Aguilarbenitez, M; Ahlen, S; Alcaraz, J; Aloisio, A; Alverson, G; Alviggi, M; Ambrosi, G; An, Q; Anderhub, H; Anderson, A; Andreev, V; et al. (1993)
The average lifetime of b hadrons has been measured using the L3 detector at LEP, running at √s ≈ MZ. A b-enriched sample was obtained from 432538 hadronic Z events collected in 1990 and 1991 by tagging electrons and muons from semileptonic b hadron decays. From maximum likelihood fits to the electron and muon impact parameter distributions, the average b hadron lifetime was measured to be τb = (1535 ± 35 ± 28) fs, where the first error is statistical and the second includes both the experimental and the theoretical systematic uncertainties. © 1993.